A comparative case study of regulatory approaches in the US and Korea - Donghee Shin; Namchul Kim; Hongsuk Yoon; Jaeyeol Jeong; Jaegil Lee (International Telecommunications Society (ITS), 2014)
In this study, we compare and contrast the U.S. and Korea in the context of network neutrality, focusing on debates among stakeholders and regulatory approaches. Interesting similarities and differences are highlighted by comparisons within the broadband ecosystem framework: government functions, histories, people's perceptions, regulatory approaches, legislative initiatives, and implementation. In Korea, there is an existing regulatory framework with suggestive guidelines that can be used to address net neutrality in a case-bycase fashion. The U.S. follows a regulatory approach by creating enforceable nondiscrimination rules. Our findings suggest that the issue is not only complicated, but also as complex and vague as the parties' diverse interests are. We conclude that a careful combination of government coordination and market forces is an effective way to govern net neutrality.
Keywords: 330; Network neutrality; comparative case study; Korea; the U.S.; broadband; competition